2010
DOI: 10.1371/journal.pone.0009815
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine Inhibits a Direct Interaction between Cyclophilins and Hepatitis C NS5A

Abstract: BackgroundHepatitis C Virus (HCV) infection is a leading indication for liver transplantation. HCV infection reoccurs almost universally post transplant, decreasing both graft longevity and patient survival. The immunosuppressant, cyclosporine A (CsA) has potent anti-HCV activity towards both HCV replicons and the genotype 2a cell culture infectious virus. Previously, we isolated mutations in the 1bN replicon with less sensitivity to CsA that mapped to both NS5A and NS5B regions of the virus. Mutations in NS5A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 37 publications
6
103
0
Order By: Relevance
“…As a control, we used GSTCypA as bait to capture full-length NS5A-His because this interaction has been shown to be direct (15)(16)(17)(18)(19)(20)(21)(22). As expected, both GST-CypA and GST-Domain I, but not GST, capture fulllength NS5A-His (Fig.…”
Section: Ns5a Forms Dimers Directly Through Domain I Interactions-mentioning
confidence: 77%
See 1 more Smart Citation
“…As a control, we used GSTCypA as bait to capture full-length NS5A-His because this interaction has been shown to be direct (15)(16)(17)(18)(19)(20)(21)(22). As expected, both GST-CypA and GST-Domain I, but not GST, capture fulllength NS5A-His (Fig.…”
Section: Ns5a Forms Dimers Directly Through Domain I Interactions-mentioning
confidence: 77%
“…NS5A is a nonstructural protein that has no defined role in the virus life cycle but is absolutely required for RNA replication (8 -10) and particle assembly (11)(12)(13)(14). It has also been shown to interact with a large number of host proteins including CypA (cyclophilin A) (15)(16)(17)(18)(19)(20)(21)(22). NS5A is peripherally anchored to membranes by an N-terminal amphipathic helix (23)(24)(25)(26)(27).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…Like other PPIases, Pin1 interacts with phosphorylated proteins through the serine/threonine-proline motif. Because both CypA and CypB interact with the HCV NS5A and NS5B proteins (2,5,10,30,35), we speculated that Pin1 might upregulate HCV propagation through interaction with either NS5A or NS5B protein. Both NS5A and NS5B are phosphoproteins that contain various phosphorylated serine/threonineproline motifs; thus, both proteins could be potential substrates of PPIases.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that both CypA and CypB interact with the NS5A and NS5B proteins and thus modulate HCV replication (2,5,10). We wondered whether these PPIases competed for interaction with HCV proteins.…”
Section: Discussionmentioning
confidence: 97%
“…However, we showed in a recent study that NS5A-D2 from the JFH-1 strain (genotype 2a) interacts with, and is a substrate for, the PPIase of human cyclophilin A (35). In addition, we could correlate the CypA interaction sites with mutations in D2 that significantly influence viral RNA replication (27) and that confer resistance to cyclophilin inhibitors (14,22,37). Finally, D3 (residues 356 -447) has been shown, at least in the context of the JFH-1 strain (2a), to be involved in the production and assembly of viral particles (26,38).…”
mentioning
confidence: 88%